Market share and market segment of public employment services - Hugh Mosley; Stefan Speckesser (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
After an introductory discussion of market share and market failure in job matching, the results of two empirical analyses are reported. The first is a cross national comparison of the importance of the public employment service (PES) as a job search channel in 12 EU states based on a special tabulation from the Eurostat Community Labour Force Survey; the second is an in-depth study of the role of the PES in job finding in Germany based on data drawn from 10 waves of the German socio-economic panel, 1984-1993. Briefly stated, the principal findings of the cross-national comparison are: 1) The PES does not primarily compete with private employment services (PRES), even in countries where they are permitted, because most job seekers use other formal and informal search channels (advertisements, direct applications to employers, friends and acquaintances etc.); 2) The clientele served by PRES is surprisingly heterogeneous and differs only in degree from that served by the PES, which suggests that PES and PRES are complementary not because they serve markedly different clienteles - as sometimes assumed - but because most PRES are temporary work agencies with similar clienteles. – – Mit der Liberalisierung der Arbeitsvermittlung und der Zulassung privater Arbeitsvermittlung in den meisten Ländern der Europäischen Union stellt sich die Frage nach der Rolle der öffentlichen Arbeitsvermittlung neu: Wie wichtig ist das Arbeitsamt heute noch im individuellen Suchprozeß auf Arbeitsmärkten für Arbeitslose und Beschäftigte? Gibt es Unterschiede zwischen den Kunden privater und öffentlicher Arbeitsvermittlung? Hilft das Arbeitsamt den Problemgruppen? Diese Fragen wurden im Forschungsprojekt Aktivierung der Arbeitsvermittlung auf Basis international vergleichbarer Daten von Eurostat untersucht. In einer vertiefenden Analyse auf Basis des sozioökonomischen Panels wurde zudem geschätzt, wie viele neue Arbeitsplätze direkt über die Vermittlung des Arbeitsamts zustande kommen und wie wichtig diese Arbeitsmarktinstitution für Zielgruppen ist.
Keywords: 330